PERAN PENGENDALIAN INTERNAL PADA AUDIT SISTEM INFORMASI DALAM SISTEM INFORMASI AKUNTANSI TERKOMPUTERISASI - ANARTA YASMITA, YULIA (Berkala Ilmiah Mahasiswa Akuntansi)
Increasingly rapid technological developments influence the change in accounting information systems from manual to a computerized accounting information systems. Given these developmental changes, provide an auditor's findings when performing their duties, still found some shortcomings or mistakes due to lack of internal control. The purpose of this paper is to describe the important role of an internal control in an information system and internal control in the presence of the auditor to evaluate the performance of a computerized accounting information systems. Auditors look at both sides of the internal control of general control or any control application. Where the auditor uses a standard implementation of COBIT (Control Objectives for Information and Related Technology) is already quite complete as the basis of examination of the information system. So hopefully after that the company can develop better information systems.